Home Equity Foreclosure Process. Is the mortgage coverage limited to the amount of the lien? - Hurtado Reyes, Martín Alejandro (2021)
The mortgage is a figure that while regulation has in the Civil Code, in which we find the estimates for its validity and effectiveness; understand however, that it develops its effects within the civil process correctly. It is here where he can find, say, the dynamic aspect of the mortgage, especially in the process of execution of guarantees. We have Article 1099, paragraph 3 of the Civil Code states that the validity of the mortgage, you must comply with one of its requirements, ie, to establish the amount of tax, which must be a fixed or determinable amount and enroll in registration of real property (property Registry today). Thus, there is no doubt that any mortgage granted to be valid must contain an amount with which it was encumbered the property in case of default of the secured obligation. No mortgage is valid if it does not contain the amount of the lien.